Collective consciousness : Art performances in the seventies - Abbalea, Martine; Acconci, Vito; Adorno, Olga; Aeschbacher, Arthur; Anderson, Laurie; Andringa, Mel; Appel, David; Atkinson, Brendan; Atlas, Charles; Baker, Robb; Banes, Sally; Barber, Nancy; et al. (New York : Performing Arts Journal Publications, 1980)
Aballéa, Martine ; Acconci, Vito ; Adorno, Olga ; Aeschbacher, Arthur ; Akalaitis, Joanne ; Alessi, Joseph ; Anderson, Laurie ; Andringa, Mel ; Appel, David ; Atkinson, Brendan ; Atlas, Charles ; Badal, Claudio ; Baker, Robb ; Banes, Sally ; Barber, Nancy ; Barth, James ; Beuchat, Carmen ; Bigelow, Kathryn ; Bittinger, Jan ; Bliss, Jayne ; Breer, Robert ; Brownell, Cara ; Buczak, Brian ; Bullock, Norvie ; Cherry, Don ; Cherry, Mocky ; Cinelli, Paul ; Cobb, Jim ; Cofone, Cesar ; Connor, Maureen ; Corber, Mitch ; Cortez, Diego ; Craven, Jay ; Crawford, Jacqueline ; Crawford, Stephen ; Davidovich, Jaime ; Deak, Edit ; DeMontaut, Philippe ; Dougherty, Frazier ; Douglas, Lea ; Downey, Juan ; Dreyfus, Charles ; Dupuy, Jean ; Edwards, Karen ; Egan, Dana ; Farina, Ralston ; Filliou, Robert ; Fiore, Bob ; Fitzgerald, Kit ; Forti, Simone ; Frank, Peter ; Frascone, Angela ; Gibson, Jon ; Girouard, Tina ; Glass, Philip ; Gold, Heloise ; Gollobin ; Greenberg, Wendy ; Greene, P.I. ; De Groat, Andy ; Haimsohn, Jana ; Halbert, Jacques ; Halleck, Dee Dee ; Halpern, Andrea ; Harris, Nancy ; Harris, Suzanne ; Harrison, Julie ; Hartnett, Elaine ; Hassel, Jon ; Hayman, Richard ; Hendricks, Geoff ; Hennessy, Timothy ; Heyward, Julia ; Higgins, Dick ; Highstein, Gene ; Hisachika ; Holt, Nancy ; de Honnecourt, Villard ; Hovagimyan, Jerry ; Howell, John ; Hubaut, Joel ; Hykes, David ; Jacobs, Ken ; James, Phil ; Jay, Paul ; Johnson, Poppy ; Johnson, Scott ; Johnson, Tom ; Jonas, Joan ; Kaplan, Philip ; Kaye, Pooh ; Knowles, Alison ; Krughoff, Fred ; Krugman, Irene ; Kubota, Shigeko ; Landry, Dicky ; Lau, Kwan ; Laugier, Emile ; Lefevre ; Lew, Jeffrey ; Lewis, Nancy ; Lindahl, Gerald ; Lundborg, Nina ; Maciunas, George ; Mantegna, Gianfranco ; Marano, Lizbeth ; de Maria, Walter ; etc.
Engels
boek